2020
DOI: 10.1002/bit.27657
|View full text |Cite
|
Sign up to set email alerts
|

Production and monitoring of biomass and fucoxanthin with brown microalgae under outdoor conditions

Abstract: The effect of light on biomass and fucoxanthin (Fx) productivities was studied in two microalgae, Tisochrysis lutea and Phaeodactylum tricornutum. High and low biomass concentrations (1.1 and 0.4 g L−1) were tested in outdoor pilot‐scale flat‐panel photobioreactors at semi‐continuous cultivation mode. Fluorescence spectroscopy coupled with chemometric modeling was used to develop prediction models for Fx content and for biomass concentration to be applied for both microalgae species. Prediction models showed h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 50 publications
(63 reference statements)
0
16
0
Order By: Relevance
“…Therefore, under conditions of nitrogen scarcity, cells tend to degrade them actively to reuse nitrogen and transfer it to the synthesis of those proteins that are indispensable for cell survival. P. tricornutum with high Fx content (0.2-16.51 mg g −1 ) has been widely concerned, which was several times more abundant than that in macroalgae (Kim et al, 2012a;Gomez-Loredo et al, 2016;Wu et al, 2016;Ishika et al, 2017;Gao et al, 2020). It has been reported that Fx content obtained from Nitzschia sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, under conditions of nitrogen scarcity, cells tend to degrade them actively to reuse nitrogen and transfer it to the synthesis of those proteins that are indispensable for cell survival. P. tricornutum with high Fx content (0.2-16.51 mg g −1 ) has been widely concerned, which was several times more abundant than that in macroalgae (Kim et al, 2012a;Gomez-Loredo et al, 2016;Wu et al, 2016;Ishika et al, 2017;Gao et al, 2020). It has been reported that Fx content obtained from Nitzschia sp.…”
Section: Discussionmentioning
confidence: 99%
“…As to Fx, the nitrogen enrichment generally promoted the accumulation of biomass and Fx content at the same time, which would undoubtedly increase Fx productivity (Sun et al, 2019). Interestingly, it was found that the higher Fx content was caused by high biomass concentration and higher biomass and Fx productivities were induced by low biomass concentration (Gao et al, 2020). These results suggested the microalgae presented different responses in terms of the productivities of lipid and Fx under nitrogen replete and limited conditions, which it was difficult to obtain high Fx and lipid productivities in the meantime.…”
Section: Discussionmentioning
confidence: 99%
“…Chemometric models for fucoxanthin content and biomass concentration of T. lutea and P. tricornutum were developed by Gao et al [63], using 2D fluorescence excitationemission matrices (EEM) obtained by off-line measurements in a cuvette as the only inputs. Biomass models predicted the BC with R 2 between 0.93 and 0.96.…”
Section: Methods Based On Fluorescence Measurementmentioning
confidence: 99%
“…Another chemometric model, mentioned already in Section 2.3.2, was developed for estimation of fucoxanthin content and biomass concentration [63]. Fucoxanthin models predicted its contents with R 2 between 0.63 and 0.77.…”
Section: Pigmentsmentioning
confidence: 99%
See 1 more Smart Citation